Experimental and numerical studies on the vibration serviceability of fanshaped prestressed concrete floor - Liang Cao; Hongtuo Qi; Jiang Li (International Journal of Distributed Sensor Networks)
An extensive experimental and numerical research was undertaken to study the vibration serviceability of a long-span fanshaped prestressed concrete floor system to be used in the lounge of a major airport. Specifically heel-drop and jumping impact tests were conducted to obtain the natural frequencies and modal damping ratios of the floor system, followed by the discussion on the distribution of peak accelerations. Running tests and simulation were also performed to capture the acceleration responses. Moreover, the finite element method was used to evaluate the dynamic characteristics. The floor system is found to have a low fundamental frequency (≈6.00 Hz) and the corresponding modal damping ratio (average ≈2.20%). The comparison of the experimental results with the published American institute of steel construction (AISC) design guide indicates that the prestressed concrete floor system exhibits satisfactory vibration perceptibility overall. The study results also show that the intensity and the location of impact excitation have a significant influence on the rate of acceleration decay. A crest factor β rp is proposed based on the test results to calculate the maximum root mean square acceleration for running for convenience.